An investigation into the origin and evolution of the Tierkloof Wetland, a peatland dominated by Prionium serratum, in the Western Cape - Bekker, Debra Jane (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The Tierkloof Wetland in the Western Cape has been damaged through erosion down to bedrock with gullies that are up to 50 m wide and 7 m deep. The purpose of this study was to investigate the origin and evolution of the Tierkloof Wetland and consider the role both natural and human-induced processes have played in its degradation. The main methods used were digital mapping using GIS software, satellite and aerial photographic interpretation of past and current land use, detailed topographic surveying, coring to bedrock, stratigraphic analysis of valley-fill sediments, and radio carbon dating of peat samples. Nine GIS-produced topographic profiles across the valley were plotted to analyse downstream changes in valley width and morphology along the length of the Tierkloof valley. Detailed cross sections of the stream channel were produced using topographic survey data. Depth to bedrock analysis indicated that there is evidence of a degree of planing of bedrock over geological time periods. Survey data indicates that the longitudinal slope of the former wetland surface is remarkably uniform over most of its length and there is an overall thinning of the valley fill from the head to the toe of the wetland. The stratigraphy and associated organic matter content of the wetland soils showed that the sedimentary fill varies considerably. There are appreciable accumulations of organic sediment, including sandy peat and peat layers with organic content of up to 50 %. The two radio carbon dates obtained from the gully wall midway down the Tierkloof Wetland suggest that peat accumulation started following the last glacial maximum. The peat has accumulated consistently and is mostly associated with the growth of the palmiet, Prionium serratum. Evidence from past and current land-use activities from aerial photographic interpretation show that natural vegetation in the Tierkloof Wetland has been severely degraded, alien plants are extremely common, and road-building and artificial drainage in the wetland have influenced fluvial processes. It is likely that these activities, exacerbated by the high rainfall events in the early 2000s, have triggered the erosional phase that was initiated a few decades ago. However, longer term processes (thousands to tens-of-thousands of years), such as the planing of the bedrock, also indicate that erosional processes have been a natural part of the Tierkloof Wetland development. A conceptual model of wetland development is thus proposed, based on long-term erosional and depositional processes that are linked with climate change and the current aggradation phase of peat formation that is being driven by the ecosystem engineering processes of palmiet plant growth. It is further suggested that relatively recent land-use activities have resulted in an already vulnerable wetland, in geomorphological terms, to cross a threshold to become a severely degraded, gulley- dominated wetland.
Keywords: Prionium serratum; Tierkloof Wetland (Western Cape, -- South Africa); Wetlands -- South Africa -- Western Cape; Aquatic plants -- South Africa -- Western Cape Cape; Peatland ecology -- South Africa -- Western Cape; Kromme River (Eastern Cape, -- South Africa)